2022
DOI: 10.1038/s41598-022-19625-3
|View full text |Cite
|
Sign up to set email alerts
|

Hall current and morphological effects on MHD micropolar non-Newtonian tri-hybrid nanofluid flow between two parallel surfaces

Abstract: In the present work, the magnetohydrodynamic flow and heat transfer of a micropolar tri-hybrid nanofluid between two porous surfaces inside a rotating system has been examined. A tri-hybrid nanofluid is a new idea in the research area, which gives a better heat transfer rate as compared to hybrid nanofluid and nanofluid. We also incorporated the thermal radiation effects and Hall current in this article. The similarity techniques are used to reduce the governing nonlinear PDEs to a set of ODEs. For the numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Thermophysical properties of a ternary nanofluid is expressed as follows [see Rauf et al (2022)] The following equations are found by using the formula (9):…”
Section: Impact Of Ternary Nanofluidmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermophysical properties of a ternary nanofluid is expressed as follows [see Rauf et al (2022)] The following equations are found by using the formula (9):…”
Section: Impact Of Ternary Nanofluidmentioning
confidence: 99%
“…Sarwar et al (2022). Guedri et al (2022), Rauf et al (2022) and Shahzad et al (2022) are among those investigators who worked on ternary nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The system (surfaces and fluid) rotates with an angular velocity in the y -axis. The flow is mathematically expressed as 51 , 52 :
Figure 1 Hybrid nanofluid flow across parallel surfaces.
…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…After detailed study, the noticed that there is a growth in the velocity profile for 0   , while the velocity is reduced with growing values of magnetic parameter and for negative values of  . Rauf et al, [14] attracted to study the magnetohydrodynamic flow and heat transfer of a micropolar tri-hybrid nanofluid between two porous surfaces inside a rotating system with the hall currents and morphological effects. The results from their studies shows the heat transfer rate of tri-hybrid nanofluid is greater than as compared to hybrid nanofluid and nanofluid.…”
Section: Introductionmentioning
confidence: 99%